The photoprotective effectiveness of microemulsion gel made from an ethanol extract of kelakai root (Stenochlaena palustris (Brum. f) bedd.) - Forestryana, Dyera; Ramadhan, Hafiz; Maulida, Puteri (Pharmacy Education, 2024)
Background: Free radicals from sunlight have detrimental effects on the skin, such as black and dull colouration and dry- and easy-to-age skin. Prevention can be done by using antioxidants derived from plants as photoprotective. Kelakai root extract has a potent antioxidant activity of 19.06 ppm. Using typical preparations in the form of microemulsion gels protects the skin from free radicals. Objective: This study aimed to determine the photoprotective effectiveness of the microemulsion gel preparation of kelakai root extract. Method: The extraction method adopted maceration with 70% ethanol solvent. The microemulsion was incorporated into a gel dosage form with a concentration of 5%. The effectiveness of the photoprotective gel was measured using UV-Vis spectrophotometry, which included determining the value of the Sun Protector Factor (SPF), erythema transmission percentage (%Te), and pigmentation transmission percentage (%Tp). Result: The results showed that the microemulsion gel of kelakai root extract with a concentration of 80 ppm had an SPF value of 9.816 with a %Te value of 9.591% and a %Tp value of 16.779%. Conclusion: The microemulsion gel of the kelakai root extract has photoprotective effectiveness as a sunscreen in the sunblock category.